Development of an integration mutagenesis system in Lactobacillus gasseri - Selle, Kurt (Landes Bioscience, 2014)
Lactobacillus gasseri ATCC 33323 is a member of the acidophilus-complex group, microbes of human origin with significant potential for impacting human health based on niche-specific traits. In order to facilitate functional analysis of this important species, a upp-based counterselective chromosomal integration system was established and employed for targeting the lipoteichoic acid (LTA) synthesis gene, ltaS, in L. gasseri ATCC 33323. The ltaS gene encodes a phosphoglycerol transferase responsible for building the glycerol chain of LTA. No isogenic mutant bearing the deletion genotype was recovered, but an integration knockout mutant was generated with insertion inactivation at the ltaS locus. The ltaS deficient derivative exhibited an altered cellular morphology and significantly reduced ability to adhere to Caco-2 intestinal cell monolayers, relative to the wild-type parent strain.